2010
DOI: 10.1111/j.1533-2500.2009.00351.x
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Target Stimulation (STS) in Chronic Noncancer Pain: A Nationwide Retrospective Study

Abstract: Stimulation of primary afferent neurons offers a new approach for the control of localized chronic pain. We describe the results with a new neurostimulation technique, subcutaneous target stimulation (STS), for the treatment of chronic focal noncancer pain. STS applies permanent electrical stimulation directly at the painful area via a percutaneous-placed subcutaneous lead. We reported the clinical outcomes of 111 patients with focal chronic, noncancer pain treated with STS in this first nationwide, multicente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
66
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 31 publications
5
66
0
4
Order By: Relevance
“…Pain scores in total decreased from 8.2 without stimulation to 4.0 with stimulation. The mean medication use was significantly reduced 69. A recent prospective multicenter study on 118 patients of PFNS on chronic low back pain showed similar results 70…”
Section: Current Technological Developmentsmentioning
confidence: 63%
See 1 more Smart Citation
“…Pain scores in total decreased from 8.2 without stimulation to 4.0 with stimulation. The mean medication use was significantly reduced 69. A recent prospective multicenter study on 118 patients of PFNS on chronic low back pain showed similar results 70…”
Section: Current Technological Developmentsmentioning
confidence: 63%
“…Interestingly, pain relief by TENS does not seem to be a predictor for the success of PFNS,71 and pain relief elicited by PNFS seems to be stronger than in TENS 69. A so-called “hybrid simulation”, combining SCS and PFNS, has also been proposed for various pain syndromes 61,62,65,67,72–74…”
Section: Current Technological Developmentsmentioning
confidence: 99%
“…Following SQS, the reduction in mean VAS ranged from 4.2 to 1.7. Five studies also reported improvements in the level of analgesia medication, [14,17-20] and three reported improvements in functional capacity compared to before SQS [13,16,18]. …”
Section: Introductionmentioning
confidence: 99%
“…Across the 3 studies reporting data, a total of 41 out of 224 (18%) patients experienced 1 or more device-related complication [14,18,19]. Risks of specific complications were as follows: lead migration, 19/245 (8%, 5 studies [14,16-19]); other lead complications (for example, fracture), 10/211 (5%, 2 studies [14,19]); hardware erosion, 0/13 (0%, 1 study [10]); infection, 9/258 (3.5%, 6 studies [12,14,17-20]); and device migration 1/113 (<1%, 2 studies [12,19]).…”
Section: Introductionmentioning
confidence: 99%
“…However, in an Austrian national study's (5) recent publication, the largest study to date, which included 111 patients, the term of “subcutaneous target stimulation” (STS) is used (11). Also, in another report by Theodosiadis et al.…”
mentioning
confidence: 99%